Sexuality Comparison in Novel Eleven Minutes With Tuhan Izinkanlah Aku Menjadi Pelacur! Memoar Luka Seorang Muslimah - Misnawati Misnawati; Lazarus Linarto; Petrus Poerwadi; Alifiah Nurachmana; Albertus Purwaka; Patrisia Cuesdeyeni; Paul Diman; Yuliati Eka Asi (Aksis : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2021)
The purpose of this research is to describe the theme of sexuality in the main character, Maria (novel "Eleven Minutes") and Kiran (novel "God allows me to become a prostitute! Memoar Luka a Muslimah"). The theory of comparative literature (comparative literature) will be the analysis knife of this research. Comparative literary theory generally emphasizes the comparison of two or more works from at least two different countries. This research will completely reveal two works from different countries. The findings of the study show: (1) the similarities in the sexuality of the characters Maria and Kiran include: (a) feeling pleasure and innocence when having intercourse; (b) having sex to fulfill biological needs; (c) Confide in each other with guests; (d) a prostitute by profession; and (e) the pay is high. (2) The differences in the themes of sexuality between Maria and Kiran include: (a) the main character Maria's sexual needs are carried out not because of a feeling of disappointment towards God but because they want to know what it is like to have a sexual adventure, while the sexual needs of the main character Kiran are used as the most basic needs because sex is made the main character as an escape from disappointment to God; (b) The main character Maria graduated from high school, while the main character Kiran is a student (c) The end of the story the main character Maria stops being a prostitute, while the main character Kiran remains a prostitute. Keywords: comparison, comparative literature, sexuality, and themes Abstrak Tujuan penelitian ini adalah mendeskripsikan tema seksualitas pada tokoh utama, Maria (novel ”Eleven Minutes”) dan Kiran (novel “Tuhan Izinkanlah Aku Menjadi Pelacur! Memoar Luka Seorang Muslimah”). Teori Sastra bandingan (comparative literature) akan menjadi pisau analisis penelitian ini. Teori sastra bandingan umumnya menekankan perbandingan dua karya atau lebih dari sedikitnya dua negara yang berbeda. Penelitian ini akan mengungkap tuntas dua buah karya dari negara yang berbeda. Temuan penelitian menunjukkan: (1) Persamaan tema seksualitas tokoh Maria dan Kiran meliputi: (a) sama-sama merasa nikmat dan tidak berdosa ketika melakukan hubungan intim; (b) melakukan seks untuk memenuhi kebutuhan biologis; (c) Saling curhat dengan tamunya; (d) berprofesi pelacur; dan (e) bayarannya mahal. (2) Perbedaaan tema seksualitas tokoh Maria dan Kiran meliputi: (a) kebutuhan seks oleh tokoh utama Maria dilakukan bukan karena pelarian rasa kecewa terhadap Tuhan tetapi karena ingin tahu bagaimana rasanya berpetualang seks, sedangkan kebutuhan seks tokoh utama Kiran dijadikan sebagai kebutuhan yang paling mendasar karena seks dijadikan tokoh utama sebagai pelarian rasa kecewa terhadap Tuhan; (b) Tokoh utama Maria lulusan SMA, sedangkan tokoh utama Kiran seorang mahasiswa (c) Akhir cerita tokoh utama Maria berhenti menjadi pelacur, sedangkan tokoh utama Kiran tetap menjadi pelacur. Kata kunci: perbandingan, sastra bandingan, seksualitas, dan tema